Negative pole piece and preparation method thereof, battery and electric equipment

By increasing the bulk density of the active layer of the negative electrode sheet, the problem of breaking active material particles in cold pressing treatment is solved, and the performance and life of the battery are improved.

CN119495707APending Publication Date: 2025-02-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311047775.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing negative electrode sheets require high pressure during the cold pressing process, resulting in the breaking of active material particles, thereby reducing the performance of the battery.

Method used

By increasing the volume density of the negative electrode active layer to be greater than 1.05 g/cm3, the pressure required during cold pressing treatment is reduced and the chance of particles to break.

Benefits of technology

Improves the battery's first-time, cycle and storage performance and extends the battery's life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495707A_ABST
    Figure CN119495707A_ABST
Patent Text Reader

Abstract

The invention discloses a negative pole piece and a preparation method thereof, a battery and electric equipment. The negative pole piece comprises a negative active layer, the negative active layer comprises a negative active material, and the volume density of the negative active material in the negative active layer of the negative pole piece which is not subjected to cold pressing treatment is greater than 1.05 g / cm < 3 >. Through the mode, the cold pressing pressure required for reaching the target compaction density during cold pressing treatment can be reduced, new surfaces and defects generated by crushing of active material particles in the cold pressing process are reduced, and then the first effect, the circulation performance and the storage performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to negative electrode sheets and preparation methods thereof, batteries and electrical equipment. Background Art

[0002] The preparation of negative electrode sheets generally includes: mixing negative electrode active materials, conductive agents, binders, etc. in proportion, adding solvent to obtain negative electrode slurry; coating the negative electrode slurry on the negative electrode collector, drying to obtain coated electrode sheets; cold pressing to obtain negative electrode sheets. In order to achieve a relatively high compaction density of the negative electrode sheets, very high pressure is often applied during the cold pressing process. Excessive pressure can easily cause the negative electrode active material particles in the sheet to break, exposing more new surfaces and defects, and thus causing the performance of the negative electrode sheets to deteriorate. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art. Summary of the invention

[0003] The main technical problem solved by the present application is to provide a negative electrode plate and a preparation method thereof, a battery and an electrical device, which can improve the initial efficiency, cycle and storage performance of the battery.

[0004] In order to solve the above technical problems, a technical solution adopted by the present application is: to provide a negative electrode sheet, the negative electrode sheet includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material, and the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05g / cm 3 ; Optionally, greater than 1.10 g / cm 3 Through this setting, the cold pressing pressure required to achieve the target compaction density during the cold pressing process can be reduced, and the new surfaces and defects generated by the crushing of active material particles during the cold pressing process can be reduced, thereby improving the initial efficiency, cycle and storage performance of the battery.

[0005] In one embodiment, the negative electrode active material includes artificial graphite, and the 5-ton compaction density of the artificial graphite is greater than 1.7 g / cm 3 ; Optional: greater than 1.8g / cm 3 In this embodiment, the compaction density of the graphite itself is large enough to make the volume density of the active layer in the coated electrode > 1.05 g / cm 3 .

[0006] In one embodiment, the tap density of the artificial graphite is 1.0-1.4 g / cm 3 , optional 1.1-1.2g / cm 3 This arrangement can reduce the microscopic edges and corners of the graphite material, reduce the probability of graphite particles breaking during cold pressing, and improve the initial efficiency, cycle life, and storage life of the manufactured battery.

[0007] In one embodiment, the median particle size Dv50 of the artificial graphite is 11-17 μm, and can be 12-16 μm. With this configuration, the particle size of the artificial graphite is relatively uniform, and the force is more uniform during cold pressing, which reduces the probability of graphite particle breakage during cold pressing, thereby improving the initial efficiency, cycle life, and storage life of the manufactured battery.

[0008] In one embodiment, the specific surface area of ​​the artificial graphite is 0.8-1.4 g / m 2 , optional 0.9-1.1g / m 2 . Adjust the specific surface area to 0.8-1.4g / m 2 , which can take into account the energy density and wettability of the material to improve the overall performance.

[0009] In order to solve the above technical problems, another technical solution adopted by the present application is: to provide a method for preparing a negative electrode sheet, the method for preparing a negative electrode sheet comprising: providing a negative electrode active material; preparing a negative electrode slurry using the negative electrode active material; forming a negative electrode active layer on a base layer using the negative electrode slurry to obtain a negative electrode sheet that has not been subjected to cold pressing, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been subjected to cold pressing is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 It can reduce the cold pressing pressure required to achieve the target compaction density during cold pressing, reduce the new surfaces and defects caused by the crushing of active material particles during the cold pressing process, and thus improve the initial efficiency, cycle and storage performance of the battery.

[0010] In order to solve the above technical problems, another technical solution adopted by the present application is: to provide a method for preparing a negative electrode sheet, the method for preparing a negative electrode sheet comprising: providing a negative electrode active material, the negative electrode active material comprising continuous graphite, the continuous graphite being a graphite material obtained by graphitizing a carbon raw material using a vertical continuous graphitization furnace; preparing a negative electrode slurry using the continuous graphite; forming a negative electrode active layer on a base layer using the negative electrode slurry to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 During the preparation of continuous graphite, the material moves from top to bottom in the furnace under the action of gravity. During the movement, it is continuously subjected to extrusion and friction forces, so that the material is processed and strengthened under these forces, so that it has a more densely packed particle size distribution and higher compressive resistance, so that the negative electrode active layer in the coated electrode has a higher volume density.

[0011] In one embodiment, the process of graphitizing the carbon raw material using a vertical continuous graphitization furnace includes: providing the carbon raw material, and putting the carbon raw material into the vertical continuous graphitization furnace; controlling the carbon raw material to enter the preheating zone of the vertical continuous graphitization furnace by gravity to preheat the raw material; feeding the preheated material into the graphitization zone of the vertical continuous graphitization furnace by gravity to graphitize the preheated material; feeding the graphitized material into the cooling zone of the vertical continuous graphitization furnace by gravity to cool the graphitized material to obtain the continuous graphite. Through this arrangement, the material moves from top to bottom in the furnace under the action of gravity, and is continuously subjected to extrusion and friction during the movement, so that the material is processed and strengthened under these forces, so that it has a more densely packed particle size distribution and higher compressive resistance, so that the negative active material in the coated pole piece has a higher volume density.

[0012] In one embodiment, the carbon raw material includes carbon particles, the carbon particles include a petroleum coke binder, and providing the carbon raw material includes: mixing the petroleum coke particles, a binder and a solvent to obtain a mixture; and pressing the mixture into a shape and drying it to obtain the petroleum coke binder. Through this arrangement, during the pressing process, the raw material particles are processed and strengthened, and the obtained continuous graphite is processed and strengthened, so that it has a more densely packed particle size distribution and a higher compressive resistance, so that the negative active layer in the coated electrode has a higher volume density.

[0013] In one embodiment, the petroleum coke particles include any one or a combination of low-sulfur coke, medium-sulfur coke, and high-sulfur coke. Through this configuration, the sulfur content in the carbon particles can be properly regulated to improve the purity of the continuous graphite, thereby improving the capacity and cycle life of the graphite.

[0014] In one embodiment, the adhesive includes any one or a combination of polyvinyl alcohol, starch, asphalt, glucose, resin, and rubber. This configuration can improve the bonding stability of the carbon particles.

[0015] In one embodiment, the volatile content of the carbon particles is less than 18% and the particle size of the carbon particles is 1 cm-8 cm. By restricting the particle size and volatile content of the carbon raw material, the smoothness of the process can be enhanced and the product yield of the graphitization process can be improved.

[0016] In one embodiment, the feeding speed of the carbon raw material is 200Kg / h-600Kg / h, and can be 300Kg / h-500Kg / h. This setting can enhance the smoothness of the process and improve the product yield of the graphitization process.

[0017] In one embodiment, the preheating zone and the graphitization zone are heated by electric heating, and the working power of the electric heating device is 600kW-1500kW, and can be 700kW-1000kW. Through this setting, the energy consumption can be reduced while maintaining the temperature of the preheating zone and the graphitization zone stable.

[0018] In one embodiment, the temperature of the preheating zone is 800° C.-1500° C. Through this arrangement, energy consumption can be reduced and the safety of process production can be improved on the basis of removing volatile components in the raw materials.

[0019] In one embodiment, the temperature of the graphitization zone is 2800° C.-3200° C. Through this configuration, the material can be graphitized to a greater extent, thereby improving the graphitization degree of the product.

[0020] In one embodiment, the preparation method further comprises rolling the continuous graphite to break it. During the rolling breaking process, the graphite particles are once again pressed, and the processing strengthening effect is further enhanced.

[0021] In one embodiment, the 5-ton compaction density of the continuous graphite is greater than 1.7 g / cm 3 ; Optional: greater than 1.8g / cm 3 In this embodiment, the compaction density of the graphite itself is large enough to increase the volume density of the active layer in the coated pole piece.

[0022] In one embodiment, the tap density of the continuous graphite is 1.0-1.4 g / cm 3 , optional 1.1-1.2g / cm 3 This arrangement can reduce the microscopic edges and corners of the graphite material, reduce the probability of graphite particles breaking during cold pressing, and improve the initial efficiency, cycle life, and storage life of the manufactured battery.

[0023] In one embodiment, the median particle size Dv50 of the continuous graphite is 11-17 μm, and can be 12-16 μm. Through this configuration, the particle size of the continuous graphite is relatively uniform, and the force is more uniform during cold pressing, which reduces the probability of graphite particle breakage during cold pressing, thereby improving the initial efficiency, cycle life, and storage life of the manufactured battery.

[0024] In one embodiment, the specific surface area of ​​the continuous graphite is 0.8-1.4 g / m 2 , optional 0.9-1.1g / m 2 . Adjust the specific surface area to 0.8-1.4g / m 2 , which can take into account the energy density and wettability of the material to improve the overall performance.

[0025] In order to solve the above technical problems, another technical solution adopted by the present application is: to provide a method for preparing a negative electrode sheet, the method for preparing a negative electrode sheet includes: providing a negative electrode active material, the negative electrode active material includes pressed graphite, the pressed graphite is a graphite material obtained by pre-pressing the front graphite, the pre-pressing pressure of the pre-pressing treatment is 100-400MPa, and can be optionally 200-300MPa, and the 5-ton compaction density of the front graphite is greater than 1.7g / cm 3 , can be selected to be greater than 1.8g / cm 3 ; Using pressed graphite to prepare negative electrode slurry; Using the negative electrode slurry to form a negative electrode active layer on a base layer to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 When the pre-pressing treatment is performed on the front graphite, the particle size distribution of the graphite particles can be optimized, making it more conducive to forming a more compact stacking state after coating, that is, the volume density of the negative electrode active layer in the negative electrode plate can be increased. If the compaction density of the front graphite itself is large enough, the pre-pressing treatment effect is good; if the compaction density of the front graphite itself is relatively small, even after the pre-pressing treatment, the volume density of the active layer in the coated electrode plate will become smaller.

[0026] In one embodiment, the holding time of the pre-pressing treatment is 30s-90s, and can be 40s-80s. If the holding time is less than 30s, the time is too short, the particle size distribution of the graphite particles is not completely adjusted, and the effect of improving the volume density after coating is limited. If the holding time is greater than 90s, the time is too long, the degree of improvement of the pressing effect is limited, and the production efficiency of the equipment is also reduced.

[0027] In one embodiment, the number of pressing times of the pre-pressing treatment is 1-8 times, and can be optionally 3-6 times. Under the described pre-pressing process, after each pressure relief, the graphite will have a certain deformation rebound. Therefore, appropriately increasing the number of pre-pressing times can cause the direction of each compression of the loaded graphite powder to be adjusted, thereby further improving the isotropy of the deformation of the graphite particles. However, if the number of pre-pressing times is too large, the graphite particles will produce more serious particle breakage under multiple compression conditions, which will reduce the initial efficiency, cycle and storage life of the battery after manufacture.

[0028] In one embodiment, the tap density of the front graphite is 1.0-1.4 g / cm 3 , optional 1.1-1.2g / cm 3 This arrangement can reduce the microscopic edges and corners of the graphite material, reduce the probability of graphite particles breaking during pre-pressing, and improve the initial efficiency, cycle life, and storage life of the manufactured battery.

[0029] In one embodiment, the median particle size Dv50 of the pre-filled graphite is 11-17 μm, and can be 12-16 μm. With this arrangement, the particle size of the pre-filled graphite is relatively uniform, and the force is more uniform during pre-pressing, which reduces the probability of graphite particle breakage during pre-pressing, thereby improving the initial efficiency, cycle life, and storage life of the manufactured battery.

[0030] In order to solve the above technical problems, another technical solution adopted by the present application is: to provide a method for preparing a negative electrode sheet, the method for preparing a negative electrode sheet comprises: providing a negative electrode active material, the negative electrode active material comprises recycled graphite, the recycled graphite is a graphite material obtained by recycling the negative electrode waste sheet, and the compaction density of the negative electrode waste sheet is greater than 1.5g / cm 3 , optional greater than 1.6g / cm 3 ; Using recycled graphite to prepare negative electrode slurry; Using the negative electrode slurry to form a negative electrode active layer on a base layer to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 . The graphite recovered from the pole piece has been cold pressed once before recycling, and the graphite particles have been processed and strengthened and the particle size distribution has been adjusted. After recycling, it is beneficial to increase the volume density of the active layer in the coated pole piece. In addition, the graphite particles recovered from the pole piece generally do not have overpressure, and the degree of particle crushing under cold pressing is not large. In addition, this process can realize waste utilization and greatly reduce production costs.

[0031] In one embodiment, the recycling of waste negative electrode sheets includes: providing waste negative electrode sheets, extracting graphite from the waste negative electrode sheets using a solvent to obtain an extract containing graphite; filtering the extract and drying it to obtain a material containing graphite; and heat treating the material containing graphite to obtain recycled graphite. The graphite recovered from the pole piece has been cold pressed once before recycling, and the graphite particles have been processed and strengthened and the particle size distribution has been adjusted. In addition, the graphite particles recovered from the pole piece generally do not have an overpressure condition, and the degree of particle crushing under cold pressing is not large. In addition, this process can realize waste utilization and greatly reduce production costs.

[0032] In one embodiment, the compaction density of the negative electrode waste sheet is greater than 1.5 g / cm 3 , optional greater than 1.6g / cm 3 The higher the compression density of the recycled negative electrode sheet, the greater the pressure it was subjected to before recycling, and the better the effect of adjusting the particle size distribution and the deformation strengthening effect.

[0033] In one embodiment, the method further comprises: rolling and crushing the recycled graphite. After the recycling heat treatment, the graphite is pressed again to further enhance the processing strengthening effect.

[0034] In one embodiment, the heat treatment temperature is greater than 400° C., and may be greater than 600° C. If the heat treatment temperature is lower than 400° C., CMC and Binder are not completely decomposed, which will result in low gram capacity of the finished graphite. If the heat treatment temperature is too high, the cost will increase significantly.

[0035] To solve the above technical problems, another technical solution adopted by the present application is to provide a battery, the battery comprising any of the above negative electrode sheets; or comprising a negative electrode sheet prepared by any of the above methods. It has high first efficiency and cycle and storage performance.

[0036] In order to solve the above technical problems, another technical solution adopted by the present application is to provide an electric device, which includes the above battery. The electric device has at least the same advantages as the battery.

[0037] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0039] Figure 1 is a schematic flow chart of a method for preparing a negative electrode sheet according to one or more embodiments;

[0040] Figure 2 is a schematic flow chart of a method for preparing artificial graphite according to one or more embodiments;

[0041] Figure 3 is a simplified structural schematic diagram of a continuous graphitization furnace according to one or more embodiments;

[0042] Figure 4 is a schematic flow chart of a method for preparing artificial graphite according to one or more embodiments;

[0043] Figure 5 is a schematic diagram of an exploded structure of a battery according to one or more embodiments;

[0044] Figure 6 is a schematic diagram of an exploded structure of a battery cell according to one or more embodiments;

[0045] Figure 7is a schematic diagram of the structure of a vehicle according to one or more embodiments.

[0046] In the attached figure:

[0047] 1000, vehicle; 300, motor; 200, controller; 100, battery; 10, housing; 11, first part; 12, second part; 20, battery cell; 21, end cap; 21a, electrode terminal; 22, housing; 23, electrode assembly. 30, continuous graphitization furnace; feed port 31; preheating zone 32; graphitization zone 33; cooling zone 34; discharge port 35; exhaust port 36. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and effect of the present application clearer and more specific, the following will describe the embodiments of the technical solution of the present application in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0050] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two), and similarly, "multiple groups" refers to more than two (including two groups), and "multiple pieces" refers to more than two (including two pieces), unless otherwise clearly and specifically defined.

[0051] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0052] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0053] Amounts, ratios and other numerical values ​​are presented herein in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or subranges encompassed within the range, as if each numerical value and subrange were explicitly specified. For example, if a range of 60-120 and 80-110 is listed for a particular parameter, it is also expected to be understood that the range of 60-110 and 80-120 is also expected. In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical value combinations.

[0054] If there is no special explanation, all steps of the present application can be performed sequentially, randomly, or in parallel, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially, or may be steps (a) and (b) performed simultaneously in parallel. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0055] The preparation of negative electrode sheets generally includes: mixing negative electrode active materials, conductive agents, binders, etc. in proportion, adding solvents to obtain negative electrode slurry; coating the negative electrode slurry on the negative electrode collector, drying to obtain coated sheets; cold pressing to obtain negative electrode sheets. In order to achieve a relatively high compaction density of the negative electrode sheets, very high pressure is often applied during the cold pressing process. Excessive pressure can easily cause the negative electrode active material particles in the sheets to break, exposing more new surfaces and defects, and thus deteriorating the performance of the negative electrode sheets. Specifically, more active ions will be consumed in the subsequent formation process of the battery preparation, which is manifested as a low initial efficiency of the battery, and poor subsequent cycle and storage performance.

[0056] The present application provides a negative electrode plate, the negative electrode plate includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material, and the volume density of the negative electrode active layer in the negative electrode plate that has not been cold pressed is greater than 1.05 g / cm 3 .

[0057] The negative electrode active layer can be expressed as a layered structure formed by the negative electrode active material as the main material, and can be specifically expressed as a layered film. The negative electrode active layer can also include a binder, a conductive agent and other optional additives. As an example, the conductive agent can be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene and carbon nanofibers. As an example, the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB). As an example, other optional additives can be thickeners and dispersants (such as sodium carboxymethyl cellulose CMC-Na), PTC thermistor materials.

[0058] The negative electrode active layer may be a layered film formed on a base layer, or may be prepared by preparing a slurry of negative electrode active material, a conductive agent, and a binder, and coating the slurry on the base layer to form the negative electrode active layer.

[0059] Among them, the base layer is a conductive base layer, which can be used as a current collector, and can be a metal foil or a composite material, for example, a composite conductive material formed by mixing a metal material with a polymer substrate. For example, aluminum foil, copper foil, etc. can be used as a metal foil. The composite conductive material may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite conductive material can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). The base layer can be in a cubic shape, having a first surface and a second surface arranged oppositely along its thickness direction, so as to support the arrangement of other layer structures. Copper foil can be selected as the base layer of the negative electrode sheet.

[0060] The active layer may be disposed only on the first surface or the second surface of the base layer, or on both the first surface and the second surface of the base layer. The active layer may be disposed directly on the surface of the base layer, or other functional material layers may be disposed between the active layer and the base layer. The active layer is the main structural layer of the electrode to realize the basic functions of the battery.

[0061] Among them, the negative electrode sheet that has not been cold pressed is a sheet obtained by coating the negative electrode slurry on the negative electrode collector and drying it; for the convenience of description, the negative electrode sheet that has not been cold pressed is referred to as a coated sheet in this article.

[0062] The cold pressing process refers to the process of using a cold pressing machine to deform the material at room temperature. The internal structure of the material will not change due to the influence of temperature during the process. During the cold pressing process, the material to be processed is placed in a die device, and then pressure is applied to change its shape. After the cold pressing process, the compaction density of the pole piece is improved. In other words, the material in the coated pole piece has not been compacted. The compaction density of the coated pole piece is less than the compaction density of the pole piece after the cold pressing process.

[0063] Volume density is the weight of a substance contained within a predetermined volume range. Volume density of negative electrode active layer = weight of negative electrode active layer / volume of negative electrode active layer, unit is g / cm 3 .

[0064] In this embodiment, the volume density of the negative electrode active layer in the coated electrode sheet is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 ; For example, it can be greater than 1.05g / cm 3 , 1.08g / cm 3 , 1.10g / cm 3 , 1.12g / cm 3 , 1.15g / cm 3 , 1.18g / cm 3 , 1.20g / cm 3 wait.

[0065] In this embodiment, the present application provides a coated electrode with a high volume density. By increasing the volume density of the negative electrode active material in the coated electrode, the cold pressing pressure required to achieve the target compaction density during the cold pressing process can be reduced, and the new surfaces and defects generated by the crushing of the active material particles during the cold pressing process can be reduced, thereby improving the initial efficiency, cycle and storage performance of the battery.

[0066] See also Figure 1 , Figure 1 1 is a schematic flow chart of a method for preparing a negative electrode sheet according to one or more embodiments. The present application provides a method for preparing a negative electrode sheet, comprising:

[0067] S410: providing a negative electrode active material.

[0068] The negative electrode active material includes but is not limited to carbon-based negative electrode materials, silicon-based negative electrode materials, tin-based negative electrode materials, lithium titanate negative electrode materials, metal lithium negative electrode materials, etc.; specifically includes but is not limited to graphite materials, silicon-carbon materials, graphite-silicon oxide materials, nano-silicon materials, silicon oxide materials and tin-based materials; more specifically includes natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or several thereof. Different types of negative electrode active materials can be selected according to the application scenario.

[0069] S420: preparing negative electrode slurry using negative electrode active materials.

[0070] The negative electrode active material, conductive agent, binder, etc. are mixed in proportion and a solvent is added to prepare the negative electrode slurry. The proportion of each material and the type of material can be adjusted according to the application requirements.

[0071] S430: forming a negative electrode active layer on the base layer using the negative electrode slurry to obtain a negative electrode sheet that has not been cold pressed.

[0072] Among them, the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05g / cm 3 .

[0073] In one embodiment, the volume density of the negative electrode active layer in the coated electrode sheet can be increased by adjusting the particle size distribution and compression resistance of the negative electrode active material. Furthermore, the negative electrode active material can be strengthened to have a more densely packed particle size distribution and higher compression resistance, so that the negative electrode active layer in the coated electrode sheet has a higher volume density.

[0074] Due to the characteristics of low cost, good thermal stability, small volume expansion rate, etc., graphite-based negative electrode materials will continue to be the mainstream negative electrode materials for batteries at present and for a long period of time in the future. Graphite-based negative electrode materials are partly derived from natural graphite and partly from artificial graphite. When artificial graphite is selected as the negative electrode active material, the properties of artificial graphite can be improved by improving the preparation process of artificial graphite.

[0075] See also Figure 2 , Figure 2 1 is a flow chart of a method for preparing artificial graphite according to one or more embodiments. The present application provides a method for preparing artificial graphite. In this embodiment, the artificial graphite includes continuous graphite, which refers to artificial graphite prepared by a continuous graphitization process. The method for preparing continuous graphite includes:

[0076] S510: providing carbon raw materials, and putting the carbon raw materials into a graphitization furnace.

[0077] The materials may be loaded manually by workers or automatically loaded by connecting to loading equipment. This application does not limit the loading method.

[0078] S520: Control the carbon raw material to enter the preheating zone of the graphitization furnace to preheat the carbon raw material.

[0079] Preheating can remove moisture, volatile matter, ash, sulfur, etc. from the carbon raw material, and other volatile impurities can also be removed.

[0080] S530: sending the preheated material into the graphitization zone of the graphitization furnace to graphitize the preheated material.

[0081] The temperature of the graphitization zone is higher than that of the preheating zone. The material is treated at high temperature in this zone so that the carbon element in the raw material is converted into a layered graphite structure at high temperature.

[0082] S540: sending the graphitized material into a cooling zone of the graphitization furnace to cool the graphitized material to obtain continuous graphite.

[0083] After graphitization is completed, it enters the cooling zone of the graphitization furnace for cooling, and the temperature gradually drops from a high temperature of about 3000°C to below 300°C, and then the material is discharged. The material is discharged after cooling to prevent the high-temperature artificial graphite from being oxidized in the air.

[0084] See also Figure 3 , Figure 3 It is a simplified structural schematic diagram of a continuous graphitization furnace according to one or more embodiments. In the method for preparing continuous graphite provided in the present application, a continuous graphitization furnace is used to graphitize a carbon raw material to obtain continuous graphite.

[0085] like Figure 3 As shown, the continuous graphitization furnace 30 includes a feed port 31, a preheating zone 32, a graphitization zone 33, a cooling zone 34, a discharge port 35, and an exhaust port 36. The preheating zone 32 and the graphitization zone 33 are provided with heating devices to heat the corresponding areas; the cooling zone 34 is provided with a condensing device to cool the corresponding areas. Figure 3 It is only a simple schematic diagram of a graphitization furnace, which is intended to reflect the main functions of the graphitization furnace. The graphitization furnace actually used in industrial production also has other components not shown in the figure, such as valves to control the feeding and discharging of materials; similarly, the size of the structure shown in the figure is not proportional, and the actual product shall prevail. This application does not limit the specific implementation method of the graphitization furnace, as long as the equipment that can realize the process of this application is acceptable.

[0086] Furthermore, in this embodiment, the continuous graphitization furnace is a vertical graphitization furnace. In the vertical direction, the feed port 31, the preheating zone 32, the graphitization zone 33, the cooling zone 34, and the discharge port 35 are distributed in order from top to bottom, so that the material can pass through the preheating zone 32, the graphitization zone 33 and the cooling zone 34 in sequence under the action of gravity.

[0087] Specifically, in the continuous graphitization process provided in the present application, the carbon raw material is put into the feed port. After the material is discharged, the material will automatically enter the preheating zone 32 for preheating by gravity. The preheated material continues to move downward by gravity to the graphitization zone 33 for high-temperature graphitization treatment; the graphitized material continues to move downward to the cooling zone 34 and can be discharged after cooling.

[0088] In this embodiment, by selecting a vertical graphitization furnace, the material moves from top to bottom in the furnace under the action of gravity, and is continuously subjected to extrusion and friction during the movement, so that the material is processed and strengthened under these forces, so that it has a more densely packed particle size distribution and higher compressive resistance, so that the negative electrode active layer in the coated electrode has a higher volume density.

[0089] Furthermore, using gravity to transfer materials can also reduce the consumption of material transportation between processes and reduce energy consumption; enhance the continuity between processes, and there is no need for intermediate stops and intermediate processing between processes, and the process can directly enter the next process, shortening the production cycle; and the preheated materials can directly enter the high-temperature zone without the need for intermediate transfer, reducing cooling and moisture regeneration during the transfer process, improving process efficiency, and reducing energy consumption.

[0090] In one embodiment, the carbon raw material includes carbon particles, and the carbon particles include petroleum coke particles or a petroleum coke binder.

[0091] Petroleum coke is a vacuum residue of petroleum, which is cracked and coked at 500-550°C in a coking unit to produce black solid coke. It is generally believed to be an amorphous carbon body or a highly aromatized high molecular carbide. According to the sulfur content in petroleum coke, it can be divided into three types: high sulfur coke, medium sulfur coke and low sulfur coke. The China Delayed Petroleum Coke Quality Standard (ZBE44002-86) divides raw coke into No. 1, No. 2 and No. 3, and each No. is divided into two categories: A coke and B coke. It is stipulated that the sulfur content of No. 1 coke is not more than 0.5% (A coke) and 0.8% (B coke), No. 2 coke is not more than 1.0% (A coke) and 1.5% (B coke), and No. 3 coke is not more than 2.0% (A coke) and 3.0% (B coke). In this embodiment, the petroleum coke particles include any one or a combination of low sulfur coke, medium sulfur coke and high sulfur coke.

[0092] In one embodiment, the carbon particles include a petroleum coke binder. Providing a carbon raw material includes:

[0093] (1) Petroleum coke particles, a binder and a solvent are mixed to obtain a mixture.

[0094] Specifically, petroleum coke particles, adhesive and solvent are added into a mixer in proportion, and stirred and dispersed evenly.

[0095] The petroleum coke particles may be any one or a combination of low-sulfur coke, medium-sulfur coke and high-sulfur coke.

[0096] The adhesive is an organic compound, and may be any one or a combination of polyvinyl alcohol, starch, asphalt, glucose, resin, and rubber.

[0097] The solvent is water.

[0098] The mixer can be any one of a horizontal ribbon mixer, a vertical ribbon mixer, a vertical VC mixer, a plowshare mixer, and a drum mixer.

[0099] (2) The mixture is pressed into shape and then dried to obtain a petroleum coke bond.

[0100] Specifically, the mixture obtained in (1) is added to a molding device to form particles with a fixed shape, and then dried in a dryer.

[0101] The forming equipment can be any one of a coal rod machine, a ring die machine, a ball press, a pelletizer, and a tablet press.

[0102] The fixed shape can be any one or a combination of short rod, sphere, cube, short sheet, and disc.

[0103] In this embodiment, during the pressing process, the raw material particles are processed and strengthened, and the resulting continuous graphite is processed and strengthened so that it has a more densely packed particle size distribution and higher compressive resistance, so that the negative electrode active layer in the coated electrode has a higher volume density.

[0104] In one embodiment, the volatile content of the carbon particles is less than 18%. Volatile matter refers to the organic matter in the sample that is heated under specified conditions in an airtight state, and decomposes into a portion of liquid with a smaller molecular weight (in a vapor state at this time). The volatile content is less than 18%, and optionally, the volatile content is less than 15%; specifically, the volatile content can be less than 18%, 15%, 13%, 11%, 10%, 8%, 5%, etc. If the volatile content is too much, the preheating treatment time will be extended, and the excessive volatiles are not easy to discharge, resulting in excessive volatile content in the final product, affecting the purity of the artificial graphite, and then affecting the capacity and life of the graphite. Furthermore, if the carbon particle raw material has too much volatile matter, it is easy to cause the material in the preheating zone 32 to coke, and the volatiles are difficult to discharge, which leads to spraying of the furnace.

[0105] In one embodiment, the particle size of the carbon particles is 1-8 cm, for example, the particle size can be 1 cm, 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, etc. If the particle size is too small, the contact surface of the particles is larger, so that the material in the preheating zone 32 is easy to coke, which makes it difficult to discharge the volatile matter, and then causes the spraying furnace; if the particle size is too large, the material feeding process is not smooth, and the volatile matter inside the carbon particles is difficult to discharge.

[0106] In this embodiment, by restricting the particle size and volatile matter of the carbon raw material, the product yield of the graphitization process can be improved, and the operational safety of the production process can be improved. The carbon raw material can be purchased commercially or prepared by itself; the raw material needs to be tested before loading to determine whether it meets the above-mentioned loading standards. If it meets the standards, it can be directly loaded. If it does not meet the standards, the raw material needs to be pretreated until it meets the above standards. For example, the particle size distribution can be controlled within 1cm to 8cm by screening through a sieve. In addition, a 1cm*1cm sieve can be used to remove fine powder before entering the furnace to prevent fine powder from entering the furnace and causing coking.

[0107] In one embodiment, the temperature of the preheating zone is 800-1500° C., and optionally, the temperature of the preheating zone may be 1000-1200° C. Specifically, it may be 800° C., 900° C., 1000° C., 1100° C., 1200° C., 1300° C., 1400° C., 1500° C., etc. Or it may be a range consisting of any two of the above values, for example, 800-1000° C., 1000-1200° C., 1200-1500° C., etc.

[0108] Preheating the raw materials can remove moisture, volatile matter, ash, sulfur and other volatile components in the raw materials. The volatile components can be discharged through the exhaust port 36. The discharged volatile matter, sulfur and ash will be drawn into the reburning chamber for combustion, and further drawn into the exhaust flue pipe and enter the exhaust gas treatment system.

[0109] Graphitization flue gas is generated in the graphitization furnace body. Once the temperature in the graphitization furnace body fluctuates greatly, these flue gases will be rapidly generated and gathered into larger flue gas clusters and flue gas layers, impacting the graphitization material channel, becoming an unstable factor in the graphitization production process, and easily leading to the occurrence of furnace spraying accidents, which brings serious safety hazards to production operators and also seriously affects the normal production.

[0110] In this embodiment, by controlling the temperature of the preheating zone, energy consumption can be reduced on the basis of removing volatiles from the raw materials. The safety of the process production is improved. If the temperature of the preheating zone is too low, the volatiles discharge speed is reduced, which easily leads to the volatiles gathering and coking in the preheating zone, and then cannot be discharged, resulting in furnace spraying. If the temperature of the preheating zone is too high, it will affect the life of the furnace cover of the continuous graphitization furnace, and more heat dissipated from the furnace cover will increase the energy consumption of the graphitization furnace.

[0111] In one embodiment, the temperature of the graphitization zone is 2800-3200°C. Optionally, the temperature of the graphitization zone may be 2900-3100°C. Specifically, it may be 2800°C, 2900°C, 3000°C, 3100°C, 3200°C, etc. Or it may be a range consisting of any two of the above values, for example, 2800-2900°C, 2900-3000°C, 3000-3100°C, 3100-3200°C, etc. By regulating the temperature of the graphitization zone, the material can be graphitized to a greater extent.

[0112] In one embodiment, the preheating zone and the graphitization zone can be heated by electric heating, electromagnetic heating, etc. The transformer can be connected to the electrode of the graphitization furnace, and the graphitization furnace can be powered on for electric heating. Controlling the output power of the transformer can control the heating effect. Among them, the power transmission (output of the transformer) of the graphitization furnace is 600kW-1500kW, optionally, the power transmission power can be 700kW-1000kW, and further 800kW-1200kW can be selected. Specifically, the power transmission power can be 600kW, 800kW, 900kW, 1000kW, 1100kW, 1200kW, 1300kW, 1400kW, 1500kW, etc. Or a range composed of any two of the above values, for example, 700kW-1000kW, 1000kW-1200kW, 1200kW-1500kW, etc. By controlling the power transmission power, energy consumption can be reduced on the basis of maintaining the temperature stability of the preheating zone and the graphitization zone. If the power supply is too low, the temperature in the graphitization furnace is low, the graphitization effect is limited, and the product graphitization degree and gram capacity are low. If the power supply is too high, the temperature in the graphitization furnace is high, the product graphitization degree and gram capacity exceed the specification, the temperature of the furnace wall refractory is high, and the life of the graphitization furnace is reduced. The power supply can be adjusted by adjusting the gear of the continuous graphitization furnace transformer.

[0113] In one embodiment, the graphitization furnace operates under an inert gas atmosphere. Specifically, nitrogen or argon is introduced as a protective gas in the preheating zone, high temperature zone, buffer zone and cooling zone of the graphitization furnace to prevent oxygen from entering. Through the protection of the inert gas, the oxygen content in the graphitization furnace can be reduced, the possibility of oxidation of the material can be reduced, and the graphitization yield can be increased and the specific surface area (BET) of graphite can be reduced.

[0114] The continuous graphitization process involves continuous inflow and outflow of materials, and the smooth flow of materials is extremely critical. However, during the continuous graphitization process, the powder material has poor fluidity in the graphitization heat treatment channel, and the accumulation of powder material leads to poor permeability of the material, resulting in high fluctuations in the removal of volatiles and flue gas emission rates, which in turn affects the stability of the flow field and temperature field of the graphitization furnace.

[0115] In one embodiment, after the raw material is put into the feed port, the rate at which the raw material is fed to the preheating zone can be controlled to regulate the reaction process. Wherein, the feed rate of the raw material is 200-600Kg / h, which can be optionally 300Kg / h-500Kg / h. For example, it can be 200Kg / h, 300Kg / h, 400Kg / h, 500Kg / h, 600Kg / h, etc. Or it is a range composed of any two of the above values, for example, 200-300Kg / h, 300-400Kg / h, 400-500Kg / h, 500-600Kg / h, etc. If the feed rate is too low, it is easy to cause coking of the material in the preheating zone, and the volatile matter is difficult to discharge, which leads to the spraying furnace. If the feed rate is too high, the time for passing through the preheating section and the graphitization section is not enough, the graphitization effect is not enough, and the high discharge temperature causes the finished graphite to oxidize. If the feeding speed is too high, the amount of volatiles accumulated in the preheating zone will be too large, which will pose a greater risk to the temperature resistance of the afterburning chamber and the flue gas treatment in the later stage. The feeding speed can be adjusted by adjusting the gear of the continuous graphitization furnace transformer.

[0116] In one embodiment, the continuous graphite may be crushed by roller pressing.

[0117] Among them, a roller press can be used to break the graphitized particles into powder under roller pressing. During the roller pressing and breaking process, the graphite particles are once again pressed, and the processing strengthening effect is further enhanced.

[0118] In one embodiment, the 5-ton compaction density of the obtained continuous graphite is greater than 1.7 g / cm 3 , can be selected to be greater than 1.8g / cm 3 .

[0119] The compaction density of 5 tons is the compaction density of artificial graphite measured under a pressure of 5 tons. The compaction density of artificial graphite under a specific pressure is a well-known meaning in the art and can be tested by methods known in the art. For example, GB / T24533-2019 can be referred to, and an electronic pressure testing machine (such as UTM7305) can be used for testing: a sample of artificial graphite powder to be tested with a preset mass M is placed on a special compaction mold (bottom area S), different pressures are set (for example, 4900N and 49000N are used in this application), the pressure is maintained for 30s, the pressure is released, and the thickness H of the powder after compaction under the pressure is read on the device. The compaction density under the pressure can be calculated, and the compaction density of the negative electrode active material under the pressure = M / (H*S).

[0120] The compacted density of graphite itself is large enough to make the volume density after coating>1.05g / cm 3 .

[0121] In one embodiment, the tap density of the obtained continuous graphite is 1.0-1.4 g / cm 3, optional 1.1-1.2g / cm 3 For example, it can be 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 wait.

[0122] Tap density refers to the mass per unit volume of the powder in the container after being tapped under specified conditions. Tap density can often reflect the microscopic morphological characteristics of the material. Generally, the larger the tap density, the easier it is for the material particles to be tightly packed, and the particles tend to be more regular, rounded and smooth. Similarly, when the tap density is small, the material particles tend to have irregular morphology and more edges and corners. Tap density is less than 1.0g / cm 3 The more edges and corners the material has at the microscopic level, the greater the probability of subsequent cold pressing and the greater the graphite particle breakage, which will reduce the initial efficiency, cycle and storage life of the battery. Therefore, the tap density of the continuous graphite should be adjusted to be greater than 1.0g / cm 3 .

[0123] In one embodiment, the median particle size Dv50 of the obtained continuous graphite is 11-17 μm, optionally 12-16 μm; for example, it can be 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, etc.

[0124] The median particle size Dv50 is greater than 17μm. The particle size is too large, and the stress is easily concentrated in a local area during cold pressing, making it difficult to form an effective and uniformly dispersed compressive stress distribution, so a good cold pressing effect cannot be achieved. The median particle size Dv50 is less than 11μm. The particle size is too small, and more small particles are easily generated during cold pressing, which will affect the initial efficiency, cycle, and storage life of the subsequent battery.

[0125] In one embodiment, the specific surface area of ​​the obtained continuous graphite is 0.8-1.4 g / m 2 , optional 0.9-1.1g / m 2 For example, it can be 0.8g / m 2 , 0.9g / m 2 1.0g / m 2 , 1.1g / m 2 , 1.2g / m 2 , 1.4g / m 2 , 1.4g / m 2 A small specific surface area is beneficial to improving the energy density of graphite materials, while a large specific surface area is beneficial to the infiltration of electrolytes; the specific surface area is regulated to 0.8-1.4g / m 2 , which can take into account both energy density and wettability to improve overall performance.

[0126] In the above, in the preparation process of continuous graphite, the artificial graphite prepared by molding-continuous graphitization-roller pressing and breaking technology is processed and strengthened during the pressing and molding process. When continuous graphitization is carried out in a vertical continuous graphitization furnace, the particles move from top to bottom in the furnace under the action of gravity. During the movement, they are continuously subjected to extrusion and friction, and the particles are continuously processed and strengthened. During the roller pressing and breaking process after graphitization, the graphite particles are once again pressed, and the processing and strengthening effect is further enhanced. Through these three key pressing and strengthening processes, the particle size is continuously adjusted to the particle size distribution most suitable for stacking, and the density of the particles themselves is continuously improved during the strengthening process. Therefore, after being coated into pole pieces, the active layer has a higher volume density.

[0127] The continuous graphite obtained in this way can be used to prepare negative electrode sheets, including:

[0128] A negative electrode active material is provided, wherein the negative electrode active material includes continuous graphite, which is a graphite material obtained by graphitizing carbon raw materials using a vertical continuous graphitization furnace; a negative electrode slurry is prepared using the continuous graphite; a negative electrode active layer is formed on a base layer using the negative electrode slurry to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 .

[0129] In one embodiment, the present application provides a method for preparing artificial graphite. In this embodiment, the artificial graphite includes pressed graphite, which is graphite that has been pre-pressed; the so-called pre-pressing means that before preparing the negative electrode slurry, the already formed graphite is first pressed once to optimize the particle size distribution of the graphite particles, so that it is more conducive to forming a more compact stacking state after coating.

[0130] Specifically, the front graphite is pre-pressed to obtain pressed graphite.

[0131] The pre-graphite can be natural graphite or artificial graphite, and can be graphite obtained by any existing preparation method, and its source is not limited here. It can also be the continuous graphite obtained above, that is, the continuous graphite can also be pre-pressed, and then the graphite is further processed and strengthened. The pre-graphite powder can be placed in a press mold, and a hydraulic press is used to apply pressure to the mold for pre-pressing.

[0132] In one embodiment, the pre-pressing pressure of the pre-pressing treatment is 100-400MPa, and can be optionally 200-300MPa. For example, it can be 100MPa, 200MPa, 300MPa, 400MPa, etc. If the pre-pressing pressure is less than 100MPa, the pressure is too small, the deformation driving force of the graphite particles is insufficient, and it is difficult to produce effective particle size distribution adjustment to improve the volume density after coating. If the pre-pressing pressure is greater than 400MPa, the pressure is too high, and the graphite particles may be severely broken under strong pressure, which will reduce the initial efficiency and cycle and storage life of the battery after it is made. The pre-pressing pressure is regulated to be in the range of 100-400MPa, preferably 200-300MPa, so that the graphite particles can produce effective deformation for adjusting the particle size distribution, and serious particle breakage will not occur.

[0133] In one embodiment, the holding time of the pre-pressing treatment is 30s-90s, and can be 40s-80s. For example, it can be 30s, 40s, 50s, 60s, 70s, 80s, etc. If the holding time is less than 30s, the time is too short, the particle size distribution adjustment of the graphite particles has not been completely completed, and the effect of improving the volume density after coating is limited. If the holding time is greater than 90s, the time is too long, the effect is limited under the long-term pressure, and the equipment production efficiency is low.

[0134] In one embodiment, the number of pressing times in the pre-pressing treatment is 1-8 times, and can be 3-6 times, for example, 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, etc.

[0135] Among them, under the described pre-pressing process, after each pressure release, the graphite will have a certain degree of deformation rebound. Therefore, appropriately increasing the number of pre-pressing times can cause the direction of each pressure applied to the loaded graphite powder to be adjusted, thereby further improving the isotropy of the deformation of the graphite particles. However, if the number of pre-pressing times is too large, the graphite particles will be severely crushed under multiple pressures, which will reduce the initial efficiency, cycle and storage life of the manufactured battery.

[0136] In one embodiment, the 5-ton compaction density of the pre-graphite is greater than 1.7 g / cm 3 , can be selected to be greater than 1.8g / cm 3 If the 5-ton compaction density of the pre-graphite itself is lower than 1.7g / cm 3 Even if the pre-pressing is increased, it is difficult to increase the volume density of the active layer in the coated electrode to 1.05g / cm 3 The 5-ton compaction density of the pre-pressed graphite is not significantly different from the 5-ton compaction density of the pre-pressed graphite, that is, the 5-ton compaction density of the pre-pressed graphite is greater than 1.7 g / cm 3 , can be selected to be greater than 1.8g / cm 3 .

[0137] In one embodiment, the tap density of the front graphite is 1.0-1.4 g / cm 3 , optional 1.1-1.2g / cm 3 For example, it can be 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 If the tap density is less than 1.0g / cm 3 The more edges and corners the material has at the microscopic level, the greater the probability of breaking under pre-compression. The larger the graphite particles are broken, the lower the initial efficiency, cycle and storage life of the battery. Therefore, the tap density of the pre-loaded graphite should be adjusted to be greater than 1.0g / cm 3 .

[0138] In one embodiment, the median particle size Dv50 of the front graphite is 11-17 μm, and can be optionally 12-16 μm; for example, it can be 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, etc.

[0139] The median particle size Dv50 is greater than 17μm. The particle size is too large, and the stress is easily concentrated in a local area during pre-pressing, making it difficult to form an effective and uniformly dispersed compressive stress distribution, so a good pre-pressing effect cannot be achieved. The median particle size Dv50 is less than 11μm. The particle size is too small, and more small particles are easily generated during pre-pressing, which will affect the initial efficiency, cycle, and storage life of the subsequent battery cells.

[0140] In one embodiment, the specific surface area of ​​the front graphite is 0.8-1.4 g / m 2 , optional 0.9-1.1g / m 2 For example, it can be 0.8g / m 2 , 0.9g / m 2 1.0g / m 2 , 1.1g / m 2 , 1.2g / m 2 , 1.4g / m 2 , 1.4g / m 2 A small specific surface area is beneficial to improving the energy density of graphite materials, while a large specific surface area is beneficial to the infiltration of electrolytes; the specific surface area is regulated to 0.8-1.4g / m 2 , which can take into account both energy density and wettability to improve overall performance.

[0141] In the above, during the preparation of pressed graphite, the already formed graphite is pressed once to optimize the particle size distribution of the graphite particles so as to make it more conducive to forming a more compact stacking state after coating.

[0142] The pressed graphite obtained in this way can be used to prepare negative electrode sheets, including:

[0143] A negative electrode active material is provided, wherein the negative electrode active material includes pressed graphite, which is a graphite material obtained by pre-pressing a pre-placed graphite, and a negative electrode slurry is prepared by using the pressed graphite; a negative electrode active layer is formed on a base layer by using the negative electrode slurry to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 .

[0144] See also Figure 4 , Figure 4 1 is a flow chart of a method for preparing artificial graphite according to one or more embodiments. The present application provides a method for preparing artificial graphite. In this embodiment, the artificial graphite includes recycled graphite, which is graphite obtained by recycling discarded negative electrode sheets. The method for preparing recycled graphite includes:

[0145] S610: providing negative electrode waste sheets.

[0146] Among them, the negative electrode waste sheets include the negative electrode waste sheets that have been cold pressed. The so-called negative electrode waste sheets that have been cold pressed refer to the negative electrode sheets that have been cold pressed before being discarded. In other words, the negative electrode sheets have been cold pressed during the preparation process, and the resulting negative electrode sheets are the negative electrode waste sheets that have been cold pressed after being discarded.

[0147] S620: extracting graphite from the negative electrode waste sheets using a solvent to obtain an extract containing graphite.

[0148] The solvent used for extraction is water. The negative electrode waste sheets may be firstly coarsely crushed to obtain negative electrode fragments, and then the electrode fragments are washed with water to obtain washing liquid; after the washing liquid is coarsely filtered, a suspension containing graphite is obtained, which is the extraction liquid.

[0149] The recycled negative electrode waste sheets can be roughly crushed by a crusher, and the size after coarse crushing is controlled to be >1cm. The obtained electrode pieces are added to a container, and an excess of deionized water is added, and stirred for washing. Subsequently, the washing liquid is roughly filtered using a 0.5cm*0.5cm filter or screen to filter out the copper foil pieces. The filtrate is a suspension containing graphite, CMC, and Binder.

[0150] S630: The extract is filtered and then dried to obtain a graphite-containing material.

[0151] The suspension is filtered by a filter press to obtain filter blocks, and the filter blocks are dried in a dryer to obtain blocks containing graphite, CMC and adhesive.

[0152] S640: heat-treating the graphite-containing material to obtain recycled graphite.

[0153] The block dried in S630 is heat treated at a temperature above 400°C. CMC and binder are decomposed at this temperature to obtain a graphite block containing only graphite. If the heat treatment temperature is lower than 400°C, CMC and binder are not completely decomposed, which will result in low gram capacity of the finished graphite. If the heat treatment temperature is too high, the cost will increase significantly.

[0154] In one embodiment, the compaction density of the negative electrode waste sheet is greater than 1.5 g / cm 3 , optional greater than 1.6g / cm 3 The higher the compression density of the recycled negative electrode sheet, the greater the pressure it was subjected to before recycling, and the better the effect of adjusting the particle size distribution and the deformation strengthening effect.

[0155] In one embodiment, the recycled graphite can also be crushed by roller pressing. The recycled graphite block is crushed by roller pressing using a double roller machine. During the crushing process, the graphite particles are once again pressed, and the processing strengthening effect is further enhanced.

[0156] In this embodiment, the graphite recovered from the pole piece has been cold pressed once before recycling, and the graphite particles have been processed and strengthened and the particle size distribution has been adjusted. After the recycling heat treatment, it is cold pressed again, which has the same technical effect. In addition, the graphite particles recovered from the pole piece generally do not have overpressure, and the degree of particle crushing under cold pressing is not large. In addition, this process can realize waste utilization and greatly reduce production costs.

[0157] The pressed graphite obtained in this way can be used to prepare negative electrode sheets, including:

[0158] A negative electrode active material is provided, wherein the negative electrode active material includes recycled graphite, and the recycled graphite is used to prepare a negative electrode slurry; the negative electrode slurry is used to form a negative electrode active layer on a base layer to obtain a negative electrode sheet that has not been cold pressed, and the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 .

[0159] In the above embodiments, graphite from different sources is strengthened to have a more densely packed particle size distribution and higher compressive resistance. The active material layer after the graphite coating has a large volume density, and a smaller force can be applied during the subsequent cold pressing process to press the pole piece to the target pressure. The reduction in cold pressing pressure can reduce the breakage of active particles during the cold pressing process, thereby improving the initial efficiency, cycle performance and storage life of the battery.

[0160] The present application also provides an electrochemical device, which includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries or secondary batteries. For example, it can be different types of secondary batteries such as lithium batteries, sodium batteries, potassium batteries, etc. Lithium secondary batteries may include lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, or lithium ion polymer secondary batteries.

[0161] Please refer to Figure 5 , Figure 5 1 is a schematic diagram of the exploded structure of a battery according to one or more embodiments. The battery 100 includes a box body 10 and a battery cell 20, and the battery cell 20 is accommodated in the box body 10. Among them, the box body 10 is used to provide a storage space for the battery cell 20, and the box body 10 can adopt a variety of structures. In some embodiments, the box body 10 may include a first part 11 and a second part 12, and the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 may be a hollow structure with one end open, and the first part 11 may be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 may also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the box body 10 formed by the first part 11 and the second part 12 may be in a variety of shapes, such as a cylinder, a cuboid, etc.

[0162] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.

[0163] Each battery cell 20 may be a secondary battery or a primary battery, or a lithium-sulfur battery, a sodium-ion battery, or a magnesium-ion battery, but is not limited thereto. The battery cell 20 may be cylindrical, flat, rectangular, or in other shapes.

[0164] Please refer to Figure 6 , Figure 6 FIG. 2 is a schematic diagram of the exploded structure of a battery cell according to one or more embodiments. A battery cell 20 is the smallest unit that constitutes a battery. Figure 6 The battery cell 20 includes an end cover 21, a shell 22, an electrode assembly 23 and other functional components.

[0165] The end cap 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cap 21 can be adapted to the shape of the shell 22 to match the shell 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 21 is not easily deformed when squeezed and collided, so that the battery cell 20 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 21a can be provided on the end cap 21. The electrode terminal 21a can be used to electrically connect to the electrode assembly 23 for outputting or inputting electrical energy of the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The material of the end cap 21 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 21, and the insulating member may be used to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.

[0166] The shell 22 is a component used to cooperate with the end cap 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the electrode assembly 23, the electrolyte and other components. The shell 22 and the end cap 21 can be independent components, and an opening can be set on the shell 22, and the internal environment of the battery cell 20 is formed by covering the opening with the end cap 21 at the opening. Without limitation, the end cap 21 and the shell 22 can also be integrated. Specifically, the end cap 21 and the shell 22 can form a common connection surface before other components are put into the shell, and when the interior of the shell 22 needs to be encapsulated, the end cap 21 covers the shell 22. The shell 22 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the electrode assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0167] The electrode assembly 23 is a component in the battery cell 100 where electrochemical reactions occur. One or more electrode assemblies 23 may be included in the housing 22. The electrode assembly 23 is mainly formed by winding or stacking positive and negative electrode sheets, and a separator is usually provided between the positive and negative electrode sheets. The parts of the positive and negative electrode sheets with active materials constitute the main body of the electrode assembly, and the parts of the positive and negative electrode sheets without active materials each constitute a tab 23a. The positive tab and the negative tab may be located together at one end of the main body or respectively at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 23a connects the electrode terminals to form a current loop.

[0168] In one embodiment, the positive electrode sheet includes a current collector and a positive active layer disposed on the current collector.

[0169] The positive electrode active layer includes a positive electrode active material, and the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0170] In one embodiment, the positive electrode active layer also includes a conductive agent to impart conductivity to the electrode. The positive electrode conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of positive electrode conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof. Optionally, the conductive agent includes one or more of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes, graphene, Ketjen black, and acetylene black.

[0171] In one embodiment, the positive electrode active layer further includes a binder to improve the adhesion stability of the active layer and reduce the probability of powder falling. The binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB). Optionally, the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, acrylate, and polyurethane.

[0172] In one embodiment, the positive electrode active layer further includes other optional additives, which may be thickeners and dispersants (such as sodium carboxymethyl cellulose CMC-Na) and PTC thermistor materials.

[0173] In some embodiments, the negative electrode plate includes a current collector and a negative electrode active layer disposed on the current collector. The negative electrode plate can be the negative electrode plate described in any of the above embodiments, which will not be described in detail here.

[0174] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0175] In one embodiment, the electrolyte includes one or more of carbonate solvents and ether solvents.

[0176] The carbonate is usually a small molecule cyclic or chain carbonate; including but not limited to one or more of ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluorocarbonate; it can also be at least one ester solvent selected from γ-butyrolactone, dimethyl sulfite, ethyl acetate, methyl acetate, methyl butyrate, ethyl butyrate, methyl propionate, ethyl propionate, propyl acetate, and fluorocarboxylic acid esters.

[0177] Ether solvents include, but are not limited to, one or more of dimethyl ether, diethyl ether, tetrahydrofuran, methyltetrahydrofuran, ethylene oxide, 1,3-dioxolane, fluoroether, DME (ethylene glycol dimethyl ether), DEE (ethylene glycol diethyl ether), DEGDME (diethylene glycol dimethyl ether), TRGDME (triethylene glycol dimethyl ether), TEGDME (tetraethylene glycol dimethyl ether), dipropyl ether and dibutyl ether.

[0178] In other embodiments, the electrolyte may also include any one or a mixture of several of an amine solvent, a sulfone solvent, and a nitrile solvent. Amine solvents include at least one of N-methylacetamide, N-methylformamide, dimethylformamide, and diethylformamide. Sulfone solvents include at least one of dimethyl sulfoxide, cyclopentane sulfone, diphenyl sulfoxide, thionyl chloride, and dipropyl sulfone. Nitrile solvents include at least one of acetonitrile, succinonitrile, adiponitrile, and glutaronitrile. The electrolyte is preferably a high-voltage resistant electrolyte, which has a weakened acidity under high voltage, can facilitate the transmission of active ions, significantly reduce side reactions on the electrode surface, and improve battery stability.

[0179] In some embodiments, the electrolyte further includes an electrolyte salt, which can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

[0180] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0181] In some embodiments, the purpose of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. The battery disclosed in the embodiment of the present application can be used for various energy storage systems using batteries as power supplies or using batteries as energy storage elements. That is, a kind of electric device is provided. In some embodiments, the electric device of the present application can be used for, but not limited to, notebook computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, ships, spacecraft, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large-scale household batteries and lithium-ion capacitors, etc.

[0182] Electrical equipment can choose battery cells, battery modules or battery packs according to its usage requirements.

[0183] Please refer to Figure 7 , Figure 7 : is a schematic diagram of the structure of a vehicle according to one or more embodiments. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, the head or the tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for the starting, navigation and working power requirements of the vehicle 1000 during driving.

[0184] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0185] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.

[0186] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0187] Example 1

[0188] (1) Preparation of positive electrode sheet

[0189] The positive electrode active material NCM523, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 96:2:2, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0190] (2) Preparation of negative electrode sheet

[0191] The negative electrode active material continuous graphite, conductive agent acetylene black, thickener CMC, and binder SBR are mixed in a mass ratio of 96.4:1:1.2:1.4, and deionized water is added as a solvent. The mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet. The volume density of the graphite after coating before cold pressing is 1.10g / cm 3 .

[0192] (3) Preparation of electrolyte

[0193] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0194] (4) Preparation of isolation membrane

[0195] A polyethylene film is selected as the separating film.

[0196] (5) Preparation of lithium-ion batteries

[0197] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0198] Example 2-3

[0199] Compared with Example 1, the process parameters and performance parameters of continuous graphitization are different, as shown in Table 1 for details.

[0200] Comparative Example 1

[0201] Compared with Example 1, the graphite used is a graphite material prepared by using an Acheson type graphitization furnace. The specific process parameters and performance parameters are detailed in Table 1.

[0202] Embodiment 4-7

[0203] Compared with Example 1, the graphite used is pressed graphite. The process parameters and performance parameters of the pressed graphite are specifically shown in Table 2.

[0204] Comparative Examples 2-4

[0205] Compared with Examples 4-7, the process parameters and performance parameters of pressed graphite are different, see Table 2 for details.

[0206] Examples 8-10

[0207] Compared with Example 1, the graphite used is recycled graphite. The process parameters and performance parameters of the recycled graphite are specifically shown in Table 3.

[0208] Comparative Example 5

[0209] Compared with Examples 8-10, the process parameters and performance parameters of the recovered graphite are different, as shown in Table 3 for details.

[0210] Performance parameter test

[0211] (1) Bulk density test

[0212] The negative electrode current collector copper foil is cut into a number of small discs with an area of ​​A, and the small discs are weighed and measured to obtain an average weight of m1 and an average thickness of h1 for the small discs of negative electrode current collector copper foil.

[0213] The negative electrode slurry is coated on the negative electrode current collector copper foil and then dried to obtain the coated negative electrode sheet. The negative electrode sheet is also cut into a number of small discs with an area of ​​A, and weighed and measured for thickness. The average weight of the coated electrode discs is m2 and the average thickness is h2.

[0214] Then the volume density after coating = (m2-m1) / [A(h2-h1)].

[0215] (2) 5 ton compaction density test

[0216] The compaction density of 5 tons is the compaction density of artificial graphite measured under a pressure of 5 tons. The compaction density of artificial graphite under a specific pressure is a well-known meaning in the art and can be tested by methods known in the art. For example, GB / T24533-2019 can be referred to, and an electronic pressure testing machine (such as UTM7305) can be used for testing: a sample of artificial graphite powder to be tested with a preset mass M is placed on a special compaction mold (bottom area S), different pressures are set (for example, 4900N and 49000N are used in this application), the pressure is maintained for 30s, the pressure is released, and the thickness H of the powder after compaction under the pressure is read on the device. The compaction density under the pressure can be calculated, and the compaction density of the negative electrode active material under the pressure = M / (H*S).

[0217] (3) Specific surface area test

[0218] According to GB / T 19587-2004 gas adsorption BET method, after the sample is heated and degassed, the adsorption amount of gas on the solid surface under different adsorption pressures is measured at a constant low temperature. The monolayer adsorption amount of the sample is obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area per unit mass of the solid sample.

[0219] (4) Dv50 test

[0220] Dv50 is the particle size corresponding to when the cumulative volume distribution percentage of artificial graphite reaches 50%, and can be tested by methods known in the art. For example, it can be measured by laser diffraction particle size analysis. It can be measured with reference to the standard GB / T 19077-2016 using a laser particle size analyzer (e.g., Malvern Master Size 3000).

[0221] (5) Tap density test

[0222] The tap density of artificial graphite is a well-known meaning in the art and can be tested by methods known in the art. For example, it can be measured using a powder tap density tester in accordance with the standard GB / T 5162-2006. For example, a FZS4-4B tap density tester of the Beijing Iron and Steel Research Institute is used, and the test parameters are as follows: vibration frequency: 250±15 times / minute, amplitude: 3±0.2 mm, vibration number: 5000 times, and measuring cylinder: 25 mL.

[0223] (6) Test of compaction density of negative electrode waste sheets

[0224] 1) Punch out the pole piece to obtain a disc sample, and measure the cross-sectional area A of the disc sample through its thickness.

[0225] 2) Weigh the mass m1 of the sample and measure the thickness d1 of the sample.

[0226] 3) Confirm the number of faces of the electrode, whether it is 1 or 2.

[0227] 4) The sample is washed with water to remove the active material and obtain a substrate.

[0228] 5) Weigh the mass m2 of the substrate and measure the thickness d2 of the substrate.

[0229] 6) The compaction density of the pole piece = (m1-m2) / [(d1-d2)*A].

[0230] (7) Cyclic performance test

[0231] The first-week cycle efficiency test includes: performing formation treatment on the static secondary battery, including: at 45°C, first charging to 3.4V with a current of 0.02C, recording the charging capacity C1 of this process; resting for 5 minutes; charging to 3.75V with a current of 0.1C, recording the charging capacity C2 of this process, and completing the formation. The formed secondary battery is transferred to a 25°C environment, charged to 4.35V with a current of 0.33C, and then charged at a constant voltage of 4.35V until the charging current is less than 0.05C, recording the charging capacity C3 of this process; resting for 5 minutes; discharging to 2.8V with a current of 0.33C, recording the discharge capacity D1 of this process; resting for 5 minutes; discharging to 0.1V with a current of 0.1C, recording the discharge capacity D2 of this process. The first-week coulombic efficiency (η) of the secondary battery is calculated according to the following formula:

[0232] η=(D1+D2) / (C1+C2+C3).

[0233] The cycle performance test process is as follows: at 25°C, the lithium ion batteries prepared in the examples and comparative examples are charged at a 1C rate and discharged at a 1C rate, and a full charge and discharge cycle test is performed until the capacity of the lithium ion battery decays to 80% of the initial capacity, and the number of cycles is recorded.

[0234] Table 1: Process performance parameters of various embodiments and comparative examples

[0235]

[0236] It can be seen from the data in Table 1 that the graphite materials in Examples 1-3 are made using a continuous graphitization process. The graphite is processed and strengthened during the preparation process, so that it has a more densely packed particle size distribution and a higher compressive resistance, so that the negative electrode active layer in the coated electrode has a higher volume density; thereby making the battery's initial efficiency and cycle performance good. In Example 1, the graphitized raw material is pressed, and the graphitized graphite material is also roll-pressed to achieve a better strengthening effect on the obtained graphite. In Comparative Example 1, a conventional graphitization process is used, and the resulting graphite material has a low degree of stacking, and the volume density of the negative electrode active layer in the resulting coated electrode is low.

[0237] Table 2: Process performance parameters of various embodiments and comparative examples

[0238]

[0239] It can be seen from the data in Table 2 that in Examples 4-7, a matching pre-pressing pressure is provided when preparing the pressed graphite, so that the graphite after pre-pressing has a more densely packed particle size distribution and higher compressive resistance, and the graphite particles are not crushed. So that the negative electrode active layer in the coated electrode has a higher volume density; thereby making the first efficiency and cycle performance of the battery good. Comparative Examples 2 and 3 give relatively small and relatively large pre-pressing pressures, so that the pressed graphite after pressing has insufficient stacking; and the 5-ton compaction density of the pre-graphite in Comparative Example 4 is relatively small, so that the stacking degree after pressing is still insufficient, the resulting graphite material has a low stacking degree, and the volume density of the negative electrode active layer in the resulting coated electrode is relatively low.

[0240] Table 3: Process performance parameters of various embodiments and comparative examples

[0241] Example 8 Example 9 Example 10 Comparative Example 5 <![CDATA[Apparent density of the negative electrode waste sheet (g / m 3 )]]> 1.75 1.70 1.75 1.45 Waste film recovery heat treatment temperature / ℃ 500 500 600 500 <![CDATA[Apparent density of 5 tons of graphite (g / m 3 )]]> 1.76 1.71 1.78 1.47 <![CDATA[Tap density of graphite (g / m 3 )]]> 1.20 1.17 1.20 0.93 Dv50 of graphite (μm) 14.6 14.4 14.5 14.3 <![CDATA[Specific surface area of graphite (g / m 2 )]]> 1.15 1.16 1.13 1.22 <![CDATA[Volume density of the negative electrode active layer (g / cm 3 )]]> 1.09 1.07 1.10 0.91 First cycle efficiency of battery / % 95.0 95.1 94.9 92.5 Battery cycle number / cycle 2980 2990 2980 2200

[0242] From the data in Table 3, it can be seen that in Examples 8-10, when recycling graphite, negative electrode waste sheets with relatively large compaction density were selected. The higher the compaction density of the recycled negative electrode sheets, the greater the pressure they were subjected to before recycling, and the better the adjustment effect on the particle size distribution and the deformation strengthening effect. The compaction density of the negative electrode waste sheets in Comparative Example 5 is relatively small, and the adjustment effect on the particle size distribution and the deformation strengthening effect are insufficient, resulting in a low volume density of the active layer of the coated electrode sheet.

[0243] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A negative electrode plate, characterized in that: include: The negative electrode active layer comprises a negative electrode active material, wherein the negative electrode active material comprises artificial graphite, and the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 ; Optionally, greater than 1.10 g / cm 3 .

2. The negative electrode sheet according to claim 1, characterized in that: The 5-ton compaction density of the artificial graphite is greater than 1.7 g / cm 3 , can be selected to be greater than 1.8g / cm 3 ; and / or The tap density of the artificial graphite is 1.0-1.4 g / cm 3 , optional 1.1-1.2g / cm 3 .

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The median particle size Dv50 of the artificial graphite is 11-17 μm, and can be 12-16 μm; The specific surface area of ​​the artificial graphite is 0.8-1.4 g / m 2 , optional 0.9-1.1g / m 2 .

4. A method for preparing a negative electrode sheet, characterized in that: include: Providing a negative electrode active material, wherein the negative electrode active material includes artificial graphite; Using the artificial graphite to prepare negative electrode slurry; The negative electrode slurry is used to form a negative electrode active layer on a base layer to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 .

5. A method for preparing a negative electrode sheet, characterized in that: include: Providing a negative electrode active material, wherein the negative electrode active material includes continuous graphite, wherein the continuous graphite is a graphite material obtained by graphitizing a carbon raw material using a vertical continuous graphitization furnace; Using the continuous graphite to prepare negative electrode slurry; The negative electrode slurry is used to form a negative electrode active layer on a base layer to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 .

6. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The graphitization treatment of carbon raw materials using a vertical continuous graphitization furnace includes: Providing a carbon raw material, and putting the carbon raw material into the vertical continuous graphitization furnace; Using gravity to control the carbon raw material to enter the preheating zone of the vertical continuous graphitization furnace to preheat the raw material; The preheated material is fed into the graphitization zone of the vertical continuous graphitization furnace by gravity to graphitize the preheated material; The graphitized material is fed into the cooling zone of the vertical continuous graphitization furnace by gravity to cool the graphitized material to obtain the continuous graphite.

7. The method for preparing a negative electrode sheet according to claim 5 or 6, characterized in that: The carbon raw material includes carbon particles, and the carbon particles include a petroleum coke binder. The providing of the carbon raw material includes: mixing petroleum coke particles, a binder and a solvent to obtain a mixture; The mixture is pressed into shape and then dried to obtain the petroleum coke adhesive.

8. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The petroleum coke particles include any one or a combination of low-sulfur coke, medium-sulfur coke, and high-sulfur coke; and / or The adhesive includes any one or a combination of polyvinyl alcohol, starch, asphalt, glucose, resin and rubber.

9. The method for preparing a negative electrode sheet according to claim 7 or 8, characterized in that: The volatile matter content of the carbon particles is less than 18%; the particle size of the carbon particles is 1 cm-8 cm.

10. The method for preparing a negative electrode sheet according to any one of claims 6 to 9, characterized in that: The method of controlling the carbon raw material to enter the preheating zone of the graphitization furnace by gravity comprises: The feeding speed of the carbon raw material is 200Kg / h-600Kg / h, and can be optionally 300Kg / h-500Kg / h.

11. The method for preparing a negative electrode sheet according to any one of claims 6 to 10, characterized in that: The preheating zone and the graphitization zone are heated by electric heating, and the working power of the electric heating device is 600kW-1500kW, and can be optionally 700kW-1000kW.

12. The method for preparing a negative electrode sheet according to any one of claims 6 to 11, characterized in that: The temperature of the preheating zone is 800°C-1500°C; and / or The temperature of the graphitization zone is 2800°C-3200°C.

13. The method for preparing a negative electrode sheet according to any one of claims 6 to 12, characterized in that: The method further comprises: The continuous graphite is crushed by roller pressing.

14. The method for preparing a negative electrode sheet according to any one of claims 5 to 13, characterized in that: The 5-ton compaction density of the continuous graphite is greater than 1.7 g / cm 3 , can be selected to be greater than 1.8g / cm 3 ; and / or The tap density of the continuous graphite is 1.0-1.4 g / cm 3 , optional 1.1-1.2g / cm 3 ; and / or The median particle size Dv50 of the continuous graphite is 11-17 μm, and can be 12-16 μm; and / or The specific surface area of ​​the continuous graphite is 0.8-1.4 g / m 2 , optional 0.9-1.1g / m 2 .

15. A method for preparing a negative electrode sheet, characterized in that: include: A negative electrode active material is provided, wherein the negative electrode active material comprises pressed graphite, wherein the pressed graphite is a graphite material obtained by pre-pressing the front graphite, wherein the pre-pressing pressure of the pre-pressing treatment is 100-400 MPa, and can be 200-300 MPa, and the 5-ton compaction density of the front graphite is greater than 1.7 g / cm 3 , can be selected to be greater than 1.8g / cm 3 ; preparing negative electrode slurry by using the pressed graphite; The negative electrode slurry is used to form a negative electrode active layer on a base layer to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 .

16. The method for preparing a negative electrode sheet according to claim 15, characterized in that: The holding time of the pre-pressing treatment is 30s-90s, and can be 40s-80s; and / or The pressing times of the pre-pressing treatment are 1-8 times, and can be optionally 3-6 times.

17. The method for preparing a negative electrode sheet according to claim 15 or 16, characterized in that: The tap density of the front graphite is 1.0-1.4 g / cm 3 , optional 1.1-1.2g / cm 3 ; and / or The median particle size Dv50 of the front graphite is 11-17 μm, and can be optionally 12-16 μm.

18. A method for preparing a negative electrode sheet, characterized in that: include: A negative electrode active material is provided, wherein the negative electrode active material comprises recycled graphite, wherein the recycled graphite is a graphite material obtained by recycling negative electrode waste sheets, and the compaction density of the negative electrode waste sheets is greater than 1.5 g / cm 3 , optional greater than 1.6g / cm 3 ; Using the recycled graphite to prepare negative electrode slurry; The negative electrode slurry is used to form a negative electrode active layer on a base layer to obtain a negative electrode sheet that has not been cold pressed, wherein the volume density of the negative electrode active layer in the negative electrode sheet that has not been cold pressed is greater than 1.05 g / cm 3 , optionally, greater than 1.10 g / cm 3 .

19. The method for preparing a negative electrode sheet according to claim 18, characterized in that: The recycling of the negative electrode waste sheets comprises: Provide negative electrode waste sheets; Extracting graphite from the negative electrode waste sheets using a solvent to obtain an extract containing graphite; The extract is filtered and then dried to obtain a graphite-containing material; The graphite-containing material is subjected to heat treatment to obtain recycled graphite.

20. The method for preparing a negative electrode sheet according to claim 19, characterized in that: The recycling of the negative electrode waste sheets also includes: The recovered graphite is crushed by roller pressing.

21. The method for preparing a negative electrode sheet according to claim 19 or 20, characterized in that: The temperature of the heat treatment is greater than 400°C, and can be optionally greater than 600°C.

22. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet as described in any one of claims 1 to 3; or a negative electrode sheet prepared by the method as described in any one of claims 4 to 21.

23. An electrical equipment, characterized in that: Comprising the battery of claim 22.